PEMBUATAN NORI RUMPUT LAUT (EUCHEUMA SPINOSUM) DENGAN PENAMBAHAN DAUN SINGKONG - Faishal, Muhammad Faishal Ammar; Maherawati; Hartanti, Lucky (Jurnal Agroindustri Pangan, 2025)
This research aims to develop a formulation that combines Eucheuma spinosum seaweed and cassava leaves to produce nori with optimal physicochemical and sensory characteristics. The method used used a completely randomized design (RAK) method with five different formulations of seaweed and cassava leaves in varying ratios, namely (60:40), (65:35), (70:30), (75:25), and (80:20). Parameters tested include water content, ash content, crude fiber content, color intensity, and organoleptic tests (color, texture, taste and aroma) to determine the best formulation. The results showed that the formulation (65 seaweed and 35 cassava leaves) achieved the best balance of physicochemical characteristics, with a water content of 9.6%, ash content of 22.7%, and crude fiber content of 21.15%. This innovative combination of Eucheuma spinosum and cassava leaves not only produces quite good quality nori but also supports food diversification based on local ingredients, increasing the value of agricultural commodities in Indonesia.